(untitled) (Journal of Engineering, 2005)
An experimental study has been carried out to investigate the possible reduction of formation damage that is result from drilling muds. This was accomplished through making a bridging system with different barite additions 70, 140, 200, 280 lb/bbl to fresh water mud. This bridging system creates an effective sealing of impermeable filter cake, thereby inhibiting continual losses of small solids and mud filtrate into the formation.The study indicates that all the truds, which were used, have the ability to damage the petrophysical properties of formation, but some additives to mud reduce the damage in petrophysical properties. In addition, it is found that minimum permeability damage can be obtained when the particles of drilling mud are larger than the pore size of formation because no internal mud cake is created. Finally, the relationship between the pore size distribution of the core samples and particle size distribution of drilling muds becomes better and the impairment is reduced, when the particle size distribution in the mud is rattched to the pore entry size distribution within the rock; so that each pore entry sould be bridged as permittal by the particular fluid flow rate involved